1992
DOI: 10.1165/ajrcmb/6.1.100
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-activating Factor Primes Human Eosinophil Generation of Superoxide

Abstract: Platelet-activating factor (PAF) is a potent inflammatory mediator that can cause airway obstruction and hyperresponsiveness; these processes are also associated with pulmonary eosinophilia, suggesting a link between these two events. Thus, PAF's interaction with eosinophils may provide a mechanism for airway damage. However, direct in vitro activation of eosinophils by PAF requires concentrations that are likely higher than those achieved in vivo. As a result, we investigated whether lower, more physiologic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1993
1993
2001
2001

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Moreover, local production of PAF appears to be important not only for the chemotaxis of EOS, but also for their in vitro activation and adhesion to endothelial cells [30,[49][50][51]. PAF is also an EOS-specific primer of cell respiratory burst when stimulated with FMLP [31]. Finally, EOS transmigration across IL-1 and IL-4 treated endothelial cell monolayers is dependent on PAF [27], while increasing the avidity of VCAM-1 binding blocks EOS migration [52].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, local production of PAF appears to be important not only for the chemotaxis of EOS, but also for their in vitro activation and adhesion to endothelial cells [30,[49][50][51]. PAF is also an EOS-specific primer of cell respiratory burst when stimulated with FMLP [31]. Finally, EOS transmigration across IL-1 and IL-4 treated endothelial cell monolayers is dependent on PAF [27], while increasing the avidity of VCAM-1 binding blocks EOS migration [52].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, endothelial cell expression of PAF, and PAF activation of CD11/CD18, is required for optimal neutrophil adhesion [28]. To determine whether PAF was involved in the development of enhanced O 2 generation by EOS adherent to IL-4 þ TNFa-stimulated HUVEC, 20 mM WEB 2086 [29,30], a PAF antagonist which was confirmed to block PAF-induced EOS O 2 generation [30,31], or buffer was added to the EOS/ HUVEC incubation. EOS adhesion to cytokine-treated HUVEC and subsequent O 2 generation to FMLP þ CB were then determined.…”
Section: Modulation Of the Enhanced O 2 Generation By Eos Adherent Tomentioning
confidence: 99%
“…Furthermore, pre-incubation with subthreshold concentrations of PAF has been demonstrated to prime the subsequent NADPH oxidase response to opsonized particles (Tool et al, 1992) and fMLP (Zoratti et al, 1992). More recent studies have demonstrated NADPH oxidase activation following human eosinophils adhesion to tissue culture plates coated with a range of extracellular matrix proteins (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…By acting on specific cell surface receptors (Hanahan, 1986;Kroegel et al, 1989b), PAF can stimulate neutrophils and eosinophils in vitro inducing chemotaxis, adhesion and degranulation (Hanahan, 1986;Wardlaw et al, 1986;Kimani et al, 1988;Czarnetzki & Csato, 1989;Kroegel et al, 1989a). In addition to activating cells directly, PAF can act as a priming agent for eosinophils (Blom et al, 1992;Zoratti et al, 1992). In vivo, intradermal administration of PAF causes neutrophil and eosinophil accumulation and oedema formation in a number of species including guineapigs (Faccioli et al, 1991), horses (Foster et al, 1992a,b), and rabbits (Wedmore & Williams, 1981b;Humphrey et al, 1982;Colditz & Movat, 1984a).…”
Section: Introductionmentioning
confidence: 99%